Pengaruh Kualitas Pelayanan dan Kepercayaan Pelanggan Terhadap Kepuasan Pengguna Transportasi Online Aplikasi Gojek di Soloraya (Studi Kasus pada Layanan Go-Ride) - Siti Aisyah; Alviana Maharani; Indah Mutiarasari; Wulan Fitri Handayani; Wella Fitra Amelia; Grezina Intan Syafilla (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
As a major player, Gojek provides many services that meet the needs of various players, with Go-Ride being the most popular service in Solo-raya. However, issues regarding customer satisfaction and trust continue to be a major concern which has an impact on user adoption levels. This type of research is quantitative research. The data processed is the results of distributing questionnaires to Gojek application users in Solo Raya. The sampling method is purposive sampling. This research uses data analysis techniques with CSI (Customer Satisfaction Index). Based on the analysis results, there is a CSI value of 85.88%. So it can be concluded that Gojek application users in Solo Raya are very satisfied with the quality of service and customer trust in the Gojek application.